2009
DOI: 10.1557/jmr.2009.0347
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ultrafine fibrous polytetrafluoroethylene porous membranes by electrospinning

Abstract: Poly(vinyl alcohol) (PVA) and poly(tetrafluoroethylene) (PTFE) emulsion were blended with different mass concentrations and the blended spinning solutions were electrospun into composite nanofibers. The influence of the blend ratio of PVA to PTFE and electrospinning technical parameters on the morphology and diameter of the composite nanofibers were investigated. According to the result of thermogravimetric analyzer analysis, the composite membrane was sintered at 390 °C. The membranes were then characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 33 publications
2
40
2
Order By: Relevance
“…23 The solution was electrospun into composite nanofibers, then sintered to obtain a PTFE porous membranes . The membranes exhibited good thermal stability and strong hydrophobicity.…”
Section: Poly(tetrafluoroethylene)mentioning
confidence: 99%
“…23 The solution was electrospun into composite nanofibers, then sintered to obtain a PTFE porous membranes . The membranes exhibited good thermal stability and strong hydrophobicity.…”
Section: Poly(tetrafluoroethylene)mentioning
confidence: 99%
“…Pyrolysis of one component of the block copolymers or the polymer colloids results in a porous structure . Peng et al showed that ultrathin carbon fibers with nanoporous structure throughout the surface and the interior of the fibers were obtained by electrospinning a mixture of PAN and a copolymer of acrylonitrile and methyl methacrylate (poly(AN‐co‐MMA)) in DMF followed by oxidizing (260–300°C, 2 h) and carbonizing (under the protection of nitrogen, 800°C, 4 h) the fibers.…”
Section: Introductionmentioning
confidence: 99%
“…So it needs more time and energy to remove the fiber-forming polymer in the following sintering processes. Xiong 14 in china prepared spinning solution by blending PVA and PTFE emulsion with different mass concentrations. Then the spinning dope was electrospun into composite nanofibers, whereby the PTFE porous membranes were obtained after sintering.…”
Section: Introductionmentioning
confidence: 99%